The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1139/v85-164
|View full text |Cite
|
Sign up to set email alerts
|

Extended basis abinitio calculations on conformers of propanal

Abstract: V. P. GUITA. Can. J. Chem. 63, 984 (1985). Extended basis ab initio calculations on four conformations of propanal at the 4-31G and 6-3 1G** levels followed by many-body perturbative interaction calculations MP2 and MP3 have been conducted. Optimized geometries, heights of rotational barriers, dipole moments, ionisation potentials, and diagonal harmonic force constants have been reported. The s-cis conformer (dihedral angle CCCO = 0") is found to be more stable than the gauche conformer (dihedral angle CCCO = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The addition of a methylene group introduces the complexity that several rotational conformers are now possible. Spectroscopic and theoretical work have shown that two stable conformers exist in the ground electronic state. , In the cis conformation, the methyl group is eclipsed with the oxygen atom (OCCC dihedral angle = 0°) whereas the skew conformation has the OCCC dihedral angle at approximately 128°. The cis conformer is found to be more stable by 5 kJ mol -1 with a barrier of 9 kJ mol -1 separating the cis and skew minima .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a methylene group introduces the complexity that several rotational conformers are now possible. Spectroscopic and theoretical work have shown that two stable conformers exist in the ground electronic state. , In the cis conformation, the methyl group is eclipsed with the oxygen atom (OCCC dihedral angle = 0°) whereas the skew conformation has the OCCC dihedral angle at approximately 128°. The cis conformer is found to be more stable by 5 kJ mol -1 with a barrier of 9 kJ mol -1 separating the cis and skew minima .…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative measurement of the width of several nonoverlapped peaks in the spectrum was made by scanning very slowly over the peak several times and averaging the scans to get a final peak profile. Measurements were performed for qRo (7), qRo (10), qRo (12), qRo(13), qRo (19), qRo (20), qPo(3), and qPo(5) transitions. The splitting of transitions corresponding to Ka ^0 prevented us from making meaningful sub-Doppler measurements as there were no cases for which both the spin-rotation and asymmetry splitting were fully resolved.…”
Section: Resultsmentioning
confidence: 99%